Heavy metals in bulk and particle size fractions from street dust of Kathmandu city as the possible basis for risk assessment - Karmacharya, Neena; Shakya, Pawan Raj (Scientific World, 2012)
Street dust has been sampled from eight major locations of Kathmandu city. The samples were separated into three particle size fractions (<425, 425-600 and >600 ?m) and analyzed for Pb, Cu, Zn and Fe using Atomic Absorption Spectrophotometric method. Results revealed that the bulk samples as well as all particle size fractions under investigation were found to have the metal abundance order as Fe > Zn > Cu > Pb. However, the trace metal concentrations increased with the decrease of dust particle size in all samples. About 35-68% of heavy metals were associated with the small particle size fraction (<425 ?m) and this particle size accounted for 64-81% of the total mass of street dust from all locations. The smaller particle size fraction has a higher heavy metal content, low density, high mobility in runoff, and thus is a higher risk for the residents of Kathmandu city. From the present study, we conclude that a monitoring plan and a suitable risk assessment are necessary to evaluate the evolution of metal concentration in dust in order to develop the proper measures for reducing the risk of inhalation and ingestion of dust for humans and environment. Scientific World, Vol. 10, No. 10, July 2012 p84-88 DOI: http://dx.doi.org/10.3126/sw.v10i10.6869